Advances in Chitosan-Based CRISPR/Cas9 Delivery Systems - Anna E. Caprifico; Peter J. S. Foot; Elena Polycarpou; Gianpiero Calabrese (MDPI AG, 2022)
Clustered regularly interspaced short palindromic repeat (CRISPR) and the associated Cas endonuclease (Cas9) is a cutting-edge genome-editing technology that specifically targets DNA sequences by using short RNA molecules, helping the endonuclease Cas9 in the repairing of genes responsible for genetic diseases. However, the main issue regarding the application of this technique is the development of an efficient CRISPR/Cas9 delivery system. The consensus relies on the use of non-viral delivery systems represented by nanoparticles (NPs). Chitosan is a safe biopolymer widely used in the generation of NPs for several biomedical applications, especially gene delivery. Indeed, it shows several advantages in the context of gene delivery systems, for instance, the presence of positively charged amino groups on its backbone can establish electrostatic interactions with the negatively charged nucleic acid forming stable nanocomplexes. However, its main limitations include poor solubility in physiological pH and limited buffering ability, which can be overcome by functionalising its chemical structure. This review offers a critical analysis of the different approaches for the generation of chitosan-based CRISPR/Cas9 delivery systems and suggestions for future developments.